Subcellular spatial regulation of immunity-induced phosphorylation of RIN4 links PAMP-triggered immunity to Exo70B1 - Zhao, Yi; Day, Brad (Frontiers in Plant Science, 2024)
RIN4 is a crucial regulator of plant immunity, playing a role in both PAMP-triggered immunity (PTI) and effector-triggered immunity (ETI). While the impact of post-translational modifications (PTMs) on RIN4 has been extensively studied, their specific effects on plant immune response regulation and the underlying mechanisms have remained unclear. In this study, we investigated the phosphorylation of RIN4 at threonine-166 (RIN4 T166 ) in Arabidopsis transgenic lines expressing various RIN4 variants. Our pathological and molecular genetic analyses reveal that RIN4 T166 phosphorylation disrupts its localization to the plasma membrane (PM) and represses plant defense activation. We found that RIN4's PM tethering relies on Exo70B1-mediated exocytosis and the integrity of the host cytoskeletal actin network. Phosphorylation at RIN4 T166 disrupts its PM localization due to reduced binding affinity with Exo70B1. This disruption was further evidenced by the 35S::RIN4 T166D /rin124 transgenic line, which exhibited suppressed PTI responses similar to the exo70b1 mutant. Our findings demonstrate that RIN4's subcellular localization is regulated by phosphorylation, suggesting that plants use a sophisticated network of signaling processes to precisely control the timing and localization of immune signaling activation.This study uncovers a mechanism by which PTI is repressed through RIN4 phosphorylation, providing new insights into the spatial regulation of RIN4 within plant immune signaling pathways.